Encountering death in the visual and verbal culture of classical Athens - Clifford, E (2022)
This thesis builds a picture of culturally-mediated encounters with death in classical Athens. Starting from the premise that death is a mystery, that no one knows what death is and what it is like, I ask two core questions. First, how does visual and verbal culture drawn from the classical period (broadly conceived, to encompass late archaic/early classical and early fourth-century material) generate encounters with death? Second, how does it prompt reflections on the imaginative processes involved in responding to death from the perspective of the living? My approach is by way of case studies, and each chapter covers a distinct medium: literary philosophy, painted pots, tragic drama, temple sculpture, and historiography.